Microfluidic technology and its application in the point-of-care testing field - Xie, Yaping; Dai, Lizhong; Yang, Yijia (Biosensors and bioelectronics. X, 2022)
Since the outbreak of the coronavirus disease 2019 (COVID-19), countries around the world have suffered heavy losses of life and property. The global pandemic poses a challenge to the global public health system, and public health organizations around the world are actively looking for ways to quickly and efficiently screen for viruses. Point-of-care testing (POCT), as a fast, portable, and instant detection method, is of great significance in infectious disease detection, disease screening, pre-disease prevention, postoperative treatment, and other fields. Microfluidic technology is a comprehensive technology that involves various interdisciplinary disciplines. It is also known as a lab-on-a-chip (LOC), and can concentrate biological and chemical experiments in traditional laboratories on a chip of several square centimeters with high integration. Therefore, microfluidic devices have become the primary implementation platform of POCT technology. POCT devices based on microfluidic technology combine the advantages of both POCT and microfluids, and are expected to shine in the biomedical field. This review introduces microfluidic technology and its applications in combination with other technologies. •The key technologies involved in microfluidic technology are introduced.•Applications of paper-based microfluidic chips and biosensors in point-of-care testing field are introduced.•The microfluidic technology and its applications in combination with other technologies in biomedical fields are described.